Preparation method and application of self-repairing polymer solid electrolyte material based on twelve hydrogen bonds
By introducing a twelve-fold hydrogen bond structure into the electrolyte material of solid-state lithium metal batteries, the problem of the battery rupture due to volume expansion and lithium dendrites during the cycle process is solved, and higher mechanical strength and self-repair ability are achieved, improving the cycle stability and safety of the battery.
Patent Information
- Application Number
- CN202510057572.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-14
AI Technical Summary
The solid polymer electrolyte materials of existing solid-state lithium metal batteries are prone to rupture due to the volume expansion of the positive electrode material and the growth of lithium dendrites during the charge and discharge cycle, which affects the circulation performance and safety of the battery.
The self-healing polymer solid electrolyte material based on twelve-hydrogen bonds is used to polymerize monomers containing ether oxygen bonds with diisocyanate, and pyridine diamine compounds are introduced to form twelve-hydrogen bonds, enhancing the interaction between polymer chains and improving the mechanical strength and self-healing ability of the material.
It significantly enhances the mechanical strength and durability of the battery, avoids short circuit problems caused by lithium dendrites, and improves the cycle stability and safety of the battery.
Smart Images

Figure CN119890430A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery solid electrolytes, and in particular to a preparation method and application of a self-repairing polymer solid electrolyte material based on dodecahydrogen bonds. Background Art
[0002] Lithium metal anode has high specific capacity (3860 mAh g -1 ) and the most negative electrochemical point, and is considered to be an ideal material to replace traditional graphite anodes and improve battery energy density, which can meet the energy density requirements of electric vehicles for portable electronic products. However, due to the flammability of organic solvents and the growth of dendrites at the lithium metal / electrolyte interface, the use of liquid electrolytes increases the safety risk of lithium metal batteries (LMBs). Therefore, the use of solid electrolytes instead of organic liquid electrolytes can effectively inhibit the growth of lithium dendrites and improve the safety of batteries, and fundamentally solve the safety problems of electric vehicles.
[0003] Inorganic solid electrolytes have high ionic conductivity and thermal stability, but are limited by severe mechanical brittleness and high electrolyte-electrode interface impedance, while solid polymer electrolytes (SPEs) have been widely studied due to their excellent mechanical flexibility and elasticity in inhibiting the growth of Li dendrites. However, the stress and strain caused by the volume expansion of the positive electrode material during the charge and discharge cycle, as well as the growth of lithium dendrites at the negative electrode, can cause the solid polymer electrolyte to rupture, seriously affecting the cycle performance of lithium metal batteries. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a preparation method and application of a self-healing polymer solid electrolyte material based on dodecahydrogen bonds. The present invention uses monomers containing ether oxygen bonds and diisocyanates as raw materials to obtain a polymer solution; introduces pyridine diamine compounds into the polymer solution to obtain a high molecular polymer solution; mixes the high molecular polymer solution with lithium salt, and then performs a coating treatment to obtain a self-healing polymer solid electrolyte material based on dodecahydrogen bonds. The self-healing polymer solid electrolyte material based on dodecahydrogen bonds prepared by the present invention has good mechanical strength, which can not only solve the internal stress problem caused by the volume expansion of the positive electrode material during the use of lithium metal batteries, but also effectively avoid the short circuit problem of lithium metal batteries caused by the growth and penetration of negative lithium dendrites, thereby greatly improving the durability and safety of the battery.
[0005] In order to achieve the above purpose, the technical solution adopted in this application is:
[0006] The first object of the present invention is to provide a method for preparing a self-healing polymer solid electrolyte material based on dodecahydrogen bonds, comprising the following steps:
[0007] S1. Mixing a monomer containing an ether oxygen bond, a diisocyanate, a catalyst and a first solvent. Under the action of the catalyst, the monomer containing an ether oxygen bond and the diisocyanate undergo a polymerization reaction to generate carbamate, thereby obtaining a polymer solution.
[0008] S2. Add a pyridinediamine compound and a second solvent to the polymer solution. The pyridinediamine compound can construct a dodecaplex hydrogen bond. After a chain extension reaction, the amino group in the pyridinediamine compound reacts with the isocyanate group in the diisocyanate to generate a urea bond. In the process of forming the urea bond, the amino group and nitrogen atom of the pyridinediamine compound act as a proton donor and a proton acceptor to participate in and form a hydrogen bond. At the same time, the pyridinediamine compound introduces multiple hydrogen bonding points into the high molecular polymer chain, thereby forming a dodecaplex hydrogen bond to obtain a high molecular polymer solution; wherein the mass ratio of the monomer containing an ether oxygen bond, the diisocyanate and the pyridinediamine compound is 80-100:8-10:1.
[0009] S3. Add lithium salt to the high molecular polymer solution to obtain an electrolyte solution; wherein the mass ratio of the high molecular polymer solution to the lithium salt is 25-30:1; if the ratio is too high, the lithium salt content is relatively small, resulting in low lithium ion conductivity; if the ratio is too low, the lithium salt is excessive, resulting in lithium salt precipitation, thereby reducing the mechanical strength of the self-healing polymer solid electrolyte material based on dodecahydrogen bonds.
[0010] S4. The electrolyte solution is coated and then dried to obtain a self-healing polymer solid electrolyte material based on dodecahydrogen bonds.
[0011] Preferably, the pyridine diamine compound is selected from at least one of 4-methoxypyridine 2,6-diamine, 2,6-diaminopyridine, 5,5'-diamino-2,2'-bipyridine, 4,4'-diamino-2,2'-bipyridine, and 1,1'(4-methoxypyridine-2,6-diyl)diurea; the pyridine of the pyridine diamine compound is connected to amino groups on both sides, and the amino groups participate in the reaction as functional groups.
[0012] Preferably, the polymerization reaction conditions are: stirring at 40° C. to 60° C. for 6 h to 10 h under the protection of an inert gas.
[0013] Preferably, the diisocyanate is selected from at least one of hexamethylene diisocyanate and toluene diisocyanate; wherein, a diisocyanate with higher symmetry is conducive to the full progress of the polymerization reaction.
[0014] Preferably, the monomer containing ether oxygen bonds is selected from at least one of tannic acid, polyethylene glycol, polytetrahydrofuran, polyester polyol, polycaprolactone, polyvinyl alcohol, and hydroxy-terminated polybutadiene.
[0015] Preferably, the amount of catalyst added is 0.2% to 1% of the mass of the polymer solution.
[0016] Preferably, the catalyst is selected from dibutyltin dilaurate, dimethylstannate, dibutylstannate or dibutyltin diacetate.
[0017] Preferably, the first solvent and the second solvent are both selected from at least one of N,N-dimethylacetamide, dichloromethane, toluene, xylene, chloroform, dimethyl carbonate, and ethylene carbonate.
[0018] Preferably, the mass ratio of the monomer containing ether oxygen bonds, the diisocyanate and the solvent is 10:1:10-20.
[0019] Preferably, the mass ratio of the pyridinediamine compound to the solvent is 1:80-100.
[0020] Preferably, the lithium salt is composed of an organic lithium salt and lithium nitrate, and the organic lithium salt is selected from lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bis(trifluoromethylsulfonyl)imide or lithium bis(fluorosulfonyl)imide; wherein lithium nitrate can construct a stable solid electrolyte phase interface on the negative electrode side and effectively stabilize the lithium metal negative electrode interface.
[0021] Preferably, the mass ratio of the organic lithium salt to lithium nitrate is 10 to 12:1; wherein, a small amount of lithium nitrate can effectively form a stable negative electrode interface protection layer to avoid side reactions, but too much lithium nitrate will precipitate from the self-healing polymer solid electrolyte material based on dodecahydrogen bonds, thereby reducing the overall mechanical properties of the self-healing polymer solid electrolyte material based on dodecahydrogen bonds.
[0022] Preferably, the drying operation is: after spreading the polymer solution on a polytetrafluoroethylene plate, drying it at 50° C. to 70° C. for 20 h to 24 h under the protection of an inert gas.
[0023] The second object of the present invention is to provide a self-repairing polymer solid electrolyte material based on dodecahydrogen bonds prepared by the above preparation method.
[0024] Preferably, the thickness of the self-healing polymer solid electrolyte material based on dodecahydrogen bonds is 50 μm to 200 μm; too high a thickness will cause the impedance of the self-healing polymer solid electrolyte material based on dodecahydrogen bonds to be too large, affecting the performance of the solid-state lithium battery; too low a thickness will cause the self-healing polymer solid electrolyte material based on dodecahydrogen bonds to be easily punctured by lithium dendrites deposited at the negative electrode of the solid-state lithium battery, causing a short circuit.
[0025] The third object of the present invention is to provide a solid-state lithium metal battery made of a positive electrode material, a negative electrode material and a self-healing polymer solid electrolyte material based on dodecahydrogen bonds.
[0026] Preferably, the positive electrode material is selected from at least one of sulfided polyacrylonitrile, sulfur-carbon composite material, lithium iron phosphate, nickel-cobalt-manganese ternary material, and lithium cobalt oxide.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1. The present invention provides a method for preparing a self-healing polymer solid electrolyte material based on dodecahydrogen bonds, comprising mixing a monomer containing an ether oxygen bond, a diisocyanate, a catalyst and a first solvent, wherein the monomer containing an ether oxygen bond and the diisocyanate are polymerized under the action of a catalyst to generate carbamate to obtain a polymer solution; a pyridine diamine compound and a second solvent are added to the polymer solution, and through a chain extension reaction, an amino group in the pyridine diamine compound reacts with an isocyanate group in the diisocyanate to generate a urea bond. In the process of forming the urea bond, the amino group and the nitrogen atom of the pyridine diamine compound serve as Proton donors and proton acceptors participate in and form hydrogen bonds, and at the same time, pyridinediamine compounds introduce multiple hydrogen bonding points into the polymer chain to form dodecaple hydrogen bonds to obtain a polymer solution; the mass ratio of monomers containing ether oxygen bonds, diisocyanates and pyridinediamine compounds is 80-100:8-10:1; lithium salt is added to the polymer solution to obtain an electrolyte solution; the mass ratio of the polymer solution to the lithium salt is 25-30:1; the electrolyte solution is coated and then dried to obtain a self-healing polymer solid electrolyte material based on dodecaple hydrogen bonds. The present invention achieves strong interaction between polymer molecular chains by introducing a monomer chain extender capable of achieving dodecahydrogen bonds, namely, pyridinediamine compounds, into the polymer chain, thereby significantly enhancing the overall mechanical strength of the self-healing polymer solid electrolyte material based on dodecahydrogen bonds. This can not only solve the internal stress problem caused by the volume expansion of the positive electrode material during the use of the solid-state lithium metal battery, but also effectively avoid the short circuit problem of the lithium metal battery caused by the growth and penetration of the negative electrode lithium dendrites, thereby greatly improving the durability and safety of the battery.
[0029] 2. The self-healing polymer solid electrolyte material based on dodecahydrogen bonds of the present invention increases the disorder of the molecular chain arrangement of the self-healing polymer solid electrolyte material based on dodecahydrogen bonds through the interaction between the carbamate group and the lithium salt and the dynamics of the dodecahydrogen bonds, and effectively reduces the crystallinity of the self-healing polymer solid electrolyte material based on dodecahydrogen bonds. This structural adjustment greatly promotes the free migration of lithium ions in the self-healing polymer solid electrolyte material based on dodecahydrogen bonds, significantly reduces the obstacles in the ion transmission process, and thus further improves the ionic conductivity of the self-healing polymer solid electrolyte material based on dodecahydrogen bonds.
[0030] In addition, the present invention also achieves efficient dissociation of lithium salts and rapid transmission of lithium ions by incorporating functional carbamate groups that can conduct lithium ions into the polymer structure. This design optimizes the ion channels inside the self-healing polymer solid electrolyte material based on dodecahydrogen bonds, reduces the energy barrier for lithium ion migration, and thus significantly improves ionic conductivity while also enhancing the overall performance of solid-state lithium metal batteries.
[0031] 3. The self-healing polymer solid electrolyte material based on dodecahydrogen bonds of the present invention has a dodecahydrogen bond structure, which gives it good interface self-healing ability. During the charge and discharge process of the solid-state lithium metal battery, if tiny cracks or damage occur, the dodecahydrogen bonds and carbamate groups in the self-healing polymer solid electrolyte material based on dodecahydrogen bonds can respond quickly and repair the damage by reforming hydrogen bonds, thereby ensuring the integrity of the interface of the solid-state lithium metal battery. This is attributed to the dynamic interaction mechanism of the breaking and recovery of hydrogen bonds between the dodecahydrogen bonds and carbamate groups within its molecules. This mechanism can not only effectively repair various interface defects and microcracks between the self-healing polymer solid electrolyte material based on dodecahydrogen bonds and the electrode, but also significantly enhance the interface compatibility of the solid-state lithium metal battery, thereby giving the solid-state lithium metal battery ultra-long cycle stability and excellent high-rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a scanning electron microscope image of the surface of the self-healing polymer solid electrolyte material based on dodecahydrogen bonds prepared in Example 10.
[0033] Figure 2 This is a scanning electron microscope image of the cross section of the self-healing polymer solid electrolyte material based on dodecahydrogen bonds prepared in Example 10.
[0034] Figure 3 This is a graph of the tensile fracture strength of the self-healing polymer solid electrolyte material based on dodecahydrogen bonds prepared in Examples 1 to 10.
[0035] Figure 4 Graphs showing the ionic conductivity of the self-healing polymer solid electrolyte materials based on dodeca-hydrogen bonds prepared in Examples 1 to 10.
[0036] Figure 5 This is a diagram of the long cycle performance of a nickel-cobalt-manganese ternary-lithium metal battery assembled with the self-healing polymer solid electrolyte material based on dodecahydrogen bonds prepared in Example 4.
[0037] Figure 6 This is a long cycle performance diagram of a nickel-cobalt-manganese ternary-lithium metal battery assembled with the self-healing polymer solid electrolyte material based on dodecahydrogen bonds prepared in Example 5.
[0038] Figure 7 This is a long cycle performance diagram of a nickel-cobalt-manganese ternary-lithium metal battery assembled with the self-healing polymer solid electrolyte material based on dodecahydrogen bonds prepared in Example 6.
[0039] Figure 8 This is a diagram of the long cycle performance of a nickel-cobalt-manganese ternary-lithium metal battery assembled with the self-healing polymer solid electrolyte material based on dodecahydrogen bonds prepared in Example 7.
[0040] Fig. 9 This is a long cycle performance diagram of a nickel-cobalt-manganese ternary-lithium metal battery assembled with the self-healing polymer solid electrolyte material based on dodecahydrogen bonds prepared in Example 8.
[0041] Fig.10 This is a diagram of the long cycle performance of a nickel-cobalt-manganese ternary-lithium metal battery assembled with the self-healing polymer solid electrolyte material based on dodecahydrogen bonds prepared in Example 9.
[0042] Fig.11 This is a diagram of the long cycle performance of a nickel-cobalt-manganese ternary-lithium metal battery assembled with the self-healing polymer solid electrolyte material based on dodecahydrogen bonds prepared in Example 10.
[0043] Fig.12 This is a diagram of the long cycle performance of a lithium-lithium symmetric battery assembled with the self-healing polymer solid electrolyte material based on dodecahydrogen bonds prepared in Example 10. DETAILED DESCRIPTION
[0044] The technical solution of the present invention will be clearly and completely described below in combination with the data in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] It should be noted that all professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.
[0046] In the existing technology, although solid polymer electrolytes (SPEs) have shown great potential in inhibiting the growth of lithium dendrites and improving battery safety, their insufficient mechanical properties and interfacial stability issues are still key factors restricting their practical application. Traditional SPEs materials often find it difficult to maintain high ionic conductivity while having sufficient mechanical strength to resist the stress challenges brought by the volume expansion of positive electrode materials and the growth of lithium dendrites. In addition, the interfacial impedance between the electrolyte and the electrode is also an important factor affecting battery performance. High interfacial impedance will lead to an increase in the internal resistance of the battery, affecting the charge and discharge efficiency and cycle stability of the battery.
[0047] In view of the problems existing in the prior art, the present invention provides a method for preparing a self-healing polymer solid electrolyte material based on dodecahydrogen bonds, comprising the following steps: mixing a monomer containing an ether oxygen bond, a diisocyanate, a catalyst and a first solvent, and under the action of a catalyst, the monomer containing an ether oxygen bond and the diisocyanate undergo a polymerization reaction to generate carbamate to obtain a polymer solution; adding a pyridine diamine compound and a second solvent to the polymer solution, and reacting the amino group in the pyridine diamine compound with the isocyanate group in the diisocyanate through a chain extension reaction to generate a urea bond; in the process of forming the urea bond, the Amino groups and nitrogen atoms act as proton donors and proton acceptors to participate in and form hydrogen bonds. At the same time, pyridinediamine compounds introduce multiple hydrogen bonding points into the polymer chain to form dodecaple hydrogen bonds, thereby obtaining a polymer solution. The mass ratio of monomers containing ether oxygen bonds, diisocyanates and pyridinediamine compounds is 80-100:8-10:1. Lithium salt is added to the polymer solution to obtain an electrolyte solution. The mass ratio of the polymer solution to the lithium salt is 25-30:1. The electrolyte solution is coated and then dried to obtain a self-healing polymer solid electrolyte material based on dodecaple hydrogen bonds.
[0048] The self-healing polymer solid electrolyte material based on dodecahydrogen bonds of the present invention has good mechanical strength, which can not only solve the internal stress problem caused by the volume expansion of the positive electrode material during the use of the lithium metal battery, but also avoid the short circuit problem of the lithium metal battery caused by the growth and penetration of lithium dendrites.
[0049] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments:
[0050] Example 1
[0051] A method for preparing a self-repairing polymer solid electrolyte material based on dodecahydrogen bonds comprises the following steps:
[0052] S1. Weigh 2.0 g of polycaprolactone and 300 μL of hexamethylene diisocyanate, dissolve them in 6 mL of toluene, add 10 μL of dibutyltin dilaurate, heat at 60° C. and stir for 1 h to obtain a clear and transparent polymer solution.
[0053] S2. Weigh 25 mg of 5,5'-diamino-2,2'-bipyridine and add it to the polymer solution, and add 2 mL of toluene to dilute it. Then, add 2 mL of toluene every hour. After stirring and reacting at 50°C for 8 hours, a polymer solution is obtained, and the molecular weight of the polymer is about 150,000.
[0054] S3. In an inert gas atmosphere, add 1 g of lithium bis(fluorosulfonyl)imide and 0.1 g of lithium nitrate to the polymer solution, and add 2 mL of toluene to obtain an electrolyte solution.
[0055] S4. In an inert gas atmosphere, evenly spread the electrolyte solution on a polytetrafluoroethylene plate and dry it at 50°C for 20 hours to obtain a self-healing polymer solid electrolyte material based on dodecahydrogen bonds. The thickness was controlled to be 200 μm and cut into discs with a diameter of 16 mm.
[0056] The self-healing polymer solid electrolyte material based on dodecahydrogen bonds prepared in Example 1 was matched with lithium metal and lithium iron phosphate positive electrodes, and the battery was assembled and left to stand for 5 hours before testing its electrochemical performance. The mass percentage of active material in the positive electrode was 80wt%, and the loading per unit area was 10mg / cm 2 .
[0057] Example 2
[0058] A method for preparing a self-repairing polymer solid electrolyte material based on dodecahydrogen bonds comprises the following steps:
[0059] S1. Weigh 2.0 g of polytetrahydrofuran and 300 μL of toluene diisocyanate, dissolve them in 6 mL of dichloromethane, add 10 μL of dibutyltin dilaurate, heat at 60° C. and stir for 1 h to obtain a clear and transparent polymer solution;
[0060] S2. Weigh 30 mg of 5,5'-diamino-2,2'-bipyridine and add it to the polymer solution, and add 2 mL of N,N-dimethylacetamide to dilute it. Then, add 2 mL of N,N-dimethylacetamide every hour. After stirring and reacting at 50°C for 8 hours, a polymer solution is obtained, and the molecular weight of the polymer is about 100,000.
[0061] S3. In an inert gas atmosphere, 1.5 g of lithium salt lithium bis(fluorosulfonyl)imide and 0.1 g of lithium nitrate were added to the polymer solution, and 2 mL of N,N-dimethylacetamide was added to obtain an electrolyte solution.
[0062] S4. In an inert gas atmosphere, evenly spread the electrolyte solution on a polytetrafluoroethylene plate, dry it at 50°C for 20 hours, and obtain a self-healing polymer solid electrolyte material based on dodecahydrogen bonds. The thickness is controlled to be 100 μm and cut into discs with a diameter of 16 mm.
[0063] The self-healing polymer solid electrolyte material based on dodecahydrogen bonds prepared in Example 2 was matched with lithium metal and lithium cobalt oxide positive electrodes, and the battery was assembled and left to stand for 5 hours before testing its electrochemical performance. The mass percentage of active material in the entire positive electrode was 80wt%, and the loading per unit area was 10mg / cm 2 .
[0064] Example 3
[0065] A method for preparing a self-repairing polymer solid electrolyte material based on dodecahydrogen bonds comprises the following steps:
[0066] S1. Weigh 3.0 g of polytetrahydrofuran and 280 μL of toluene diisocyanate, dissolve them in 6 mL of dichloromethane, add 15 μL of dibutyltin dilaurate, heat at 60° C. and stir for 1 h to obtain a clear and transparent polymer solution.
[0067] S2. Weigh 30 mg of 2,6-diaminopyridine and add it to the polymer solution, and add 2 mL of N,N-dimethylacetamide to dilute it. Then, add 2 mL of N,N-dimethylacetamide every hour. After stirring and reacting at 50°C for 8 hours, a polymer solution is obtained, and the molecular weight of the polymer is about 200,000.
[0068] S3. In an inert gas atmosphere, 1.2 g of lithium salt lithium bis(fluorosulfonyl)imide and 0.3 g of lithium nitrate were added to the polymer solution, and 2 mL of N,N-dimethylacetamide was added to obtain an electrolyte solution.
[0069] S4. In an inert gas atmosphere, evenly spread the electrolyte solution on a polytetrafluoroethylene plate and dry it at 50°C for 20 hours to obtain a self-healing polymer solid electrolyte material based on dodecahydrogen bonds. The thickness was controlled to be 150 μm and cut into discs with a diameter of 16 mm.
[0070] The self-healing polymer solid electrolyte material based on dodecahydrogen bonds prepared in Example 3 was matched with lithium metal and nickel-cobalt-manganese ternary positive electrodes, and the battery was assembled and left to stand for 5 hours before testing its electrochemical performance. The mass percentage of active material in the entire positive electrode was 80wt%, and the loading per unit area was 20mg / cm 2 .
[0071] Example 4
[0072] A method for preparing a self-repairing polymer solid electrolyte material based on dodecahydrogen bonds comprises the following steps:
[0073] S1. Weigh 2.0 g of polyethylene glycol and 200 μL of toluene diisocyanate, dissolve them in 6 mL of dichloromethane, add 20 μL of dibutyltin dilaurate, heat at 60° C. and stir for 1 h to obtain a clear and transparent polymer solution.
[0074] S2. Weigh 40 mg of 2,6-diaminopyridine and add it to the polymer solution, and add 2 mL of N,N-dimethylacetamide to dilute it. Then, add 2 mL of N,N-dimethylacetamide every hour. After stirring and reacting at 50°C for 8 hours, a polymer solution is obtained, and the molecular weight of the polymer is about 250,000.
[0075] S3. In an inert gas atmosphere, add 1 g of lithium salt lithium bis(fluorosulfonyl)imide and 0.1 g of lithium nitrate to the polymer solution, and add 2 mL of N,N-dimethylacetamide to obtain an electrolyte solution.
[0076] S4. In an inert gas atmosphere, evenly spread the electrolyte solution on a polytetrafluoroethylene plate and dry it at 50°C for 20 hours to obtain a self-healing polymer solid electrolyte material based on dodecahydrogen bonds. The thickness was controlled to be 180 μm and cut into discs with a diameter of 16 mm.
[0077] The self-healing polymer solid electrolyte material based on dodecahydrogen bonds prepared in Example 4 was matched with lithium metal and nickel-cobalt-manganese ternary positive electrodes, and the battery was assembled and left to stand for 5 hours before testing its electrochemical performance. The mass percentage of active material in the entire positive electrode was 80wt%, and the loading per unit area was 20mg / cm 2 .
[0078] Example 5
[0079] A method for preparing a self-repairing polymer solid electrolyte material based on dodecahydrogen bonds comprises the following steps:
[0080] S1. Weigh 2.0 g of polyethylene glycol and 200 μL of hexamethylene diisocyanate, dissolve them in 10 mL of dichloromethane, add 20 μL of dibutyltin dilaurate, heat at 60° C. and stir for 1 h to obtain a clear and transparent polymer solution.
[0081] S2. Weigh 25 mg of 5,5'-diamino-2,2'-bipyridine and add it to the polymer solution, and add 2 mL of N,N-dimethylacetamide to dilute it. Then, add 2 mL of N,N-dimethylacetamide every hour. After stirring and reacting at 50°C for 8 hours, a polymer solution is obtained, and the molecular weight of the polymer is about 250,000.
[0082] S3. In an inert gas atmosphere, add 1 g of lithium salt lithium bis(fluorosulfonyl)imide and 0.1 g of lithium nitrate to the polymer solution, and add 2 mL of N,N-dimethylacetamide to obtain an electrolyte solution.
[0083] S4. In an inert gas atmosphere, evenly spread the electrolyte solution on a polytetrafluoroethylene plate and dry it at 50°C for 20 hours to obtain a self-healing polymer solid electrolyte material based on dodecahydrogen bonds. The thickness was controlled to be 150 μm and cut into discs with a diameter of 16 mm.
[0084] The self-healing polymer solid electrolyte material based on dodecahydrogen bonds prepared in Example 5 was matched with lithium metal and nickel-cobalt-manganese ternary positive electrodes, and the battery was assembled and left to stand for 5 hours before testing its electrochemical performance. The mass percentage of active material in the entire positive electrode was 80wt%, and the loading per unit area was 20mg / cm 2 .
[0085] Example 6
[0086] A method for preparing a self-repairing polymer solid electrolyte material based on dodecahydrogen bonds comprises the following steps:
[0087] S1. Weigh 3.0 g of tannic acid and 150 μL of hexamethylene diisocyanate, dissolve them in 6 mL of ethylene carbonate, add 10 μL of dibutyltin dilaurate, heat at 60° C. and stir for 1 h to obtain a clear and transparent polymer solution.
[0088] S2. Weigh 25 mg of 2,6-diaminopyridine and add it to the polymer solution, and add 2 mL of ethylene carbonate to dilute it. Then, add 2 mL of ethylene carbonate every hour. After stirring and reacting at 50° C. for 8 hours, a polymer solution is obtained, and the molecular weight of the polymer is about 300,000.
[0089] S3. In an inert gas atmosphere, 1.5 g of lithium salt lithium bis(fluorosulfonyl)imide and 0.1 g of lithium nitrate were added to the polymer solution, and 2 mL of ethylene carbonate was added to obtain an electrolyte solution.
[0090] S4. In an inert gas atmosphere, evenly spread the electrolyte solution on a polytetrafluoroethylene plate and dry it at 50°C for 20 hours to obtain a self-healing polymer solid electrolyte material based on dodecahydrogen bonds. The thickness was controlled to be 200 μm and cut into discs with a diameter of 16 mm.
[0091] The self-healing polymer solid electrolyte material based on dodecahydrogen bonds prepared in Example 6 was matched with lithium metal and nickel-cobalt-manganese ternary positive electrodes, and the battery was assembled and left to stand for 5 hours before testing its electrochemical performance. The mass percentage of active material in the entire positive electrode was 80wt%, and the loading per unit area was 20mg / cm 2 .
[0092] Example 7
[0093] A method for preparing a self-repairing polymer solid electrolyte material based on dodecahydrogen bonds comprises the following steps:
[0094] S1. Weigh 2.5 g of polytetrahydrofuran and 180 μL of toluene diisocyanate, dissolve them in 6 mL of dichloromethane, add 10 μL of dibutyltin dilaurate, heat at 60° C. and stir for 1 h to obtain a clear and transparent polymer solution.
[0095] S2. Weigh 30 mg of 4,4'-diamino-2,2'-bipyridine and add it to the polymer solution, and add 2 mL of N,N-dimethylacetamide to dilute it. Then, add 2 mL of N,N-dimethylacetamide every hour. After stirring and reacting at 50°C for 8 hours, a polymer solution is obtained, and the molecular weight of the polymer is about 400,000.
[0096] S3. In an inert gas atmosphere, 1.5 g of lithium salt bis(trifluoromethylsulfonyl)imide lithium and 0.3 g of lithium nitrate were added to the polymer solution, and 2 mL of N,N-dimethylacetamide was added to obtain an electrolyte solution.
[0097] S4. In an inert gas atmosphere, evenly spread the electrolyte solution on a polytetrafluoroethylene plate and dry it at 50°C for 20 hours to obtain a self-healing polymer solid electrolyte material based on dodecahydrogen bonds. The thickness was controlled to be 200 μm and cut into discs with a diameter of 16 mm.
[0098] The self-healing polymer solid electrolyte material based on dodecahydrogen bonds prepared in Example 7 was matched with lithium metal and nickel-cobalt-manganese ternary positive electrodes. The mass percentage of active material in the entire positive electrode was 80wt%, and the loading per unit area was 20mg / cm 2 , assemble the battery and test its electrochemical performance after standing for 5h.
[0099] Example 8
[0100] A method for preparing a self-repairing polymer solid electrolyte material based on dodecahydrogen bonds comprises the following steps:
[0101] S1. Weigh 2.0 g of polyvinyl alcohol and 250 μL of hexamethylene diisocyanate, dissolve them in 10 mL of xylene, add 10 μL of dibutyltin dilaurate, heat at 60° C. and stir for 1 h to obtain a clear and transparent polymer solution.
[0102] S2. Weigh 30 mg of 4,4'-diamino-2,2'-bipyridine and add it to the polymer solution, and add 2 mL of N,N-dimethylacetamide to dilute it. Then, add 2 mL of N,N-dimethylacetamide every hour. After stirring and reacting at 50°C for 8 hours, a polymer solution is obtained, and the molecular weight of the polymer is about 450,000.
[0103] S3. In an inert gas atmosphere, 0.8 g of lithium salt bis(trifluoromethylsulfonyl)imide lithium and 0.2 g of lithium nitrate were added to the polymer solution, and 2 mL of N,N-dimethylacetamide was added to obtain an electrolyte solution.
[0104] S4. In an inert gas atmosphere, evenly spread the electrolyte solution on a polytetrafluoroethylene plate, dry it at 50°C for 20 hours, and obtain a self-healing polymer solid electrolyte material based on dodecahydrogen bonds. The thickness is controlled to be 100 μm and cut into discs with a diameter of 16 mm.
[0105] The self-healing polymer solid electrolyte material based on dodecahydrogen bonds prepared in Example 8 was matched with lithium metal and nickel-cobalt-manganese ternary positive electrodes. The mass percentage of active material in the entire positive electrode was 80wt%, and the loading per unit area was 20mg / cm 2 , assemble the battery and test its electrochemical performance after standing for 5h.
[0106] Example 9
[0107] A method for preparing a self-repairing polymer solid electrolyte material based on dodecahydrogen bonds comprises the following steps:
[0108] S1. Weigh 2.5 g of polytetrahydrofuran and 300 μL of hexamethylene diisocyanate, dissolve them in 10 mL of dichloromethane, add 10 μL of dibutyltin dilaurate, heat at 60° C. and stir for 1 h to obtain a clear and transparent polymer solution.
[0109] S2. Weigh 30 mg of 4,4'-diamino-2,2'-bipyridine and add it to the polymer solution, and add 2 mL of N,N-dimethylacetamide to dilute it. Then, add 2 mL of N,N-dimethylacetamide every hour. After stirring and reacting at 50°C for 8 hours, a polymer solution is obtained, and the molecular weight of the polymer is about 500,000.
[0110] S3. In an inert gas atmosphere, 1.2 g of lithium salt bis(trifluoromethylsulfonyl)imide lithium and 0.2 g of lithium nitrate were added to the polymer solution, and 2 mL of N,N-dimethylacetamide was added to obtain an electrolyte solution.
[0111] S4. In an inert gas atmosphere, evenly spread the electrolyte solution on a polytetrafluoroethylene plate and dry it at 50°C for 20 hours to obtain a self-healing polymer solid electrolyte material based on dodecahydrogen bonds. The thickness was controlled to be 200 μm and cut into discs with a diameter of 16 mm.
[0112] The self-healing polymer solid electrolyte material based on dodecahydrogen bonds prepared in Example 9 was matched with lithium metal and nickel-cobalt-manganese ternary positive electrodes. The mass percentage of active material in the entire positive electrode was 80wt%, and the loading per unit area was 10mg / cm 2 , assemble the battery and test its electrochemical performance after standing for 5h.
[0113] Example 10
[0114] A method for preparing a self-repairing polymer solid electrolyte material based on dodecahydrogen bonds comprises the following steps:
[0115] S1. Weigh 2.0 g of polytetrahydrofuran and 220 μL of hexamethylene diisocyanate, dissolve them in 6 mL of dichloromethane, add 10 μL of dibutyltin dilaurate, heat at 60° C. and stir for 1 h to obtain a clear and transparent polymer solution.
[0116] S2. Weigh 25 mg of 2,6-diaminopyridine and add it to the polymer solution, and add 2 mL of N,N-dimethylacetamide to dilute it. Then, add 2 mL of N,N-dimethylacetamide every hour. After stirring and reacting at 50°C for 8 hours, a polymer solution is obtained, and the molecular weight of the polymer is about 600,000.
[0117] S3. In an inert gas atmosphere, 0.9 g of lithium salt lithium bis(fluorosulfonyl)imide and 0.2 g of lithium nitrate were added to the polymer solution, and 2 mL of N,N-dimethylacetamide was added to obtain an electrolyte solution.
[0118] S4. In an inert gas atmosphere, evenly spread the electrolyte solution on a polytetrafluoroethylene plate and dry it at 50°C for 20 hours to obtain a self-healing polymer solid electrolyte material based on dodecahydrogen bonds. The thickness was controlled to be 50 μm and cut into discs with a diameter of 16 mm.
[0119] The self-healing polymer solid electrolyte material based on dodecahydrogen bonds prepared in Example 10 is matched with lithium metal and nickel-cobalt-manganese ternary positive electrodes.
[0120] The self-healing polymer solid electrolyte material based on dodeca-hydrogen bonds prepared in Example 10 was matched with lithium metal to assemble a lithium-lithium symmetric battery. After standing for 5 hours, its electrochemical performance was tested.
[0121] The mass percentage of active material in the entire positive electrode is 80wt%, and the loading per unit area is 10mg / cm 2 , assemble the battery and test its electrochemical performance after standing for 5h.
[0122] a. Transverse rupture strength test: The self-healing polymer solid electrolyte material based on dodecahydrogen bonds prepared in Examples 1 to 10 was cut into a cross-sectional area of 1 mm 2 , a rectangular piece with a length of 50 mm was subjected to tensile test at a rate of 5 mm / min using a tensile testing machine.
[0123] Lithium metal battery assembly: Lithium metal batteries were assembled using the self-healing polymer solid electrolyte materials based on dodecahydrogen bonds prepared in Examples 1 to 10. The lithium metal battery used a commercial lithium sheet with a diameter of 16 mm as the negative electrode, and selected sulfurized polyacrylonitrile, sulfur-carbon composite material, lithium iron phosphate, nickel-cobalt-manganese ternary material and lithium cobalt oxide as the positive electrode, and a battery shell with a model of CR2032 was selected for assembly.
[0124] b. Ionic conductivity test: Test the electrochemical impedance spectroscopy (EIS) of lithium metal batteries, and analyze and evaluate the impedance results to calculate the corresponding ionic conductivity.
[0125] c. Cycle performance test: After the assembled lithium metal battery was left to stand for 5 hours, the cycle performance test was performed at 25°C. The first two cycles were charged and discharged at a rate of 0.2C to activate the lithium metal battery, and then the charge and discharge cycle test was performed at a rate of 0.5C or 1C.
[0126] observe Figure 1It is concluded that the surface of the self-healing polymer solid electrolyte material based on dodecahydrogen bonds prepared in Example 10 of the present invention is smooth and dense, and can significantly improve the interface contact performance between the self-healing polymer solid electrolyte material based on dodecahydrogen bonds and the positive electrode and the negative electrode.
[0127] observe Figure 2 It is concluded that the self-healing polymer solid electrolyte material based on dodecahydrogen bonds prepared in Example 10 of the present invention has a dense cross-section and a non-porous structure, which is beneficial for preventing the growth of lithium dendrites.
[0128] observe Figure 3 and Figure 4 It is concluded that Example 10 uses polytetrahydrofuran, hexamethylene diisocyanate and 2,6-diaminopyridine as reactants, lithium bis(fluorosulfonyl)imide and lithium nitrate are selected as lithium salts, and N,N-dimethylacetamide is used as solvent. The self-healing polymer solid electrolyte material based on dodecahydrogen bonds has a higher transverse rupture strength of up to 69 MPa and an ionic conductivity of 6.5×10 -4 S / cm.
[0129] In terms of mechanical strength, as the molecular weight of the polymer increases, the mechanical strength of the self-healing polymer solid electrolyte material based on twelve-fold hydrogen bonds increases. The reaction ratio of polytetrahydrofuran to hexamethylene diisocyanate and the amount of 2,6-diaminopyridine added in Example 10 optimize the molecular weight and intermolecular force of the self-healing polymer solid electrolyte material based on twelve-fold hydrogen bonds, thereby improving the tensile strength. In terms of ionic conductivity, the lithium salt concentration and the crystallinity of the polymer in the self-healing polymer solid electrolyte material based on twelve-fold hydrogen bonds have a significant effect on ionic conductivity. The ratio of lithium bis(fluorosulfonyl)imide and lithium nitrate in Example 10 provides the optimal ion migration number and conductivity. In terms of self-healing ability, the introduction of twelve-fold hydrogen bonds provides a dynamic cross-linked network for the self-healing polymer solid electrolyte material based on twelve-fold hydrogen bonds, so that the self-healing polymer solid electrolyte material based on twelve-fold hydrogen bonds can achieve self-healing by breaking and reorganizing hydrogen bonds when damaged, which is poor in other embodiments due to the small number of hydrogen bonds.
[0130] Depend on Figure 5 , Figure 6 , Figure 7 , Figure 8 , Fig. 9 , Fig.10 as well as Fig.11The results show the influence of different reactants and reaction ratios on the cycle performance of nickel-cobalt-manganese ternary positive electrode batteries. Among them, the nickel-cobalt-manganese ternary positive electrode battery assembled with the self-healing polymer solid electrolyte material based on twelve-fold hydrogen bonds prepared in Example 10 still maintains a capacity retention rate of 93% after 700 cycles, indicating that the self-healing polymer solid electrolyte material based on twelve-fold hydrogen bonds prepared in Example 10 can effectively inhibit the growth of lithium dendrites and the decomposition of the electrolyte during repeated charge and discharge, and maintain good cycle stability. In other embodiments, due to inappropriate reactants or reaction ratios, the electrolyte is insufficiently stable, the capacity decays rapidly, and the cycle performance is poor.
[0131] In terms of the selection of reactants, the combination of polytetrahydrofuran, hexamethylene diisocyanate and 2,6-diaminopyridine used in Example 10 can form a self-healing polymer solid electrolyte material based on dodecahydrogen bonds with high ionic conductivity, thereby improving the cycle performance of the nickel-cobalt-manganese ternary positive electrode battery. The introduction of dodecahydrogen bonds enables the self-healing polymer solid electrolyte material based on dodecahydrogen bonds to have self-healing ability, which can repair tiny cracks during the charge and discharge process and maintain good interface stability, thereby improving the cycle life of the nickel-cobalt-manganese ternary positive electrode battery.
[0132] In terms of the influence of the reaction ratio, the mass ratio of the polymer solution to the lithium salt in Example 10 is 2:1, which optimizes the migration channel of lithium ions and improves the ionic conductivity and cycle performance of the nickel-cobalt-manganese ternary positive electrode battery. A relatively high lithium salt concentration helps to improve the ionic conductivity of the self-healing polymer solid electrolyte material based on twelve-fold hydrogen bonds, but an excessively high ratio will cause the lithium salt to precipitate, affecting the performance of the nickel-cobalt-manganese ternary positive electrode battery.
[0133] In Example 10, the ratio of polymer to chain extender in the polymer solution is 80:8:1, which ensures the mechanical strength and self-healing ability of the self-healing polymer solid electrolyte material based on dodecahydrogen bonds, while ensuring its good ionic conductivity.
[0134] Depend on Fig.12 The results show that the lithium-lithium symmetric battery of Example 10 has long cycle characteristics and excellent performance, with a cycle time of up to 1400h, indicating that the self-healing and healing function of the self-healing polymer solid electrolyte material based on dodecahydrogen bonds prepared in Example 10 enables the interface integrity of the battery to be maintained well, thereby having excellent cycle performance. This is because polytetrahydrofuran, hexamethylene diisocyanate and 2,6-diaminopyridine have the strongest reactivity, and the self-healing polymer solid electrolyte material based on dodecahydrogen bonds prepared has the highest polymer molecular weight. In lithium-lithium batteries, when the current density is increased to 0.4mA / cm -2When the polarization voltage of the lithium-lithium battery begins to decrease, it means that the self-healing polymer solid electrolyte material based on dodecahydrogen bonds is repairing the interface defects. By breaking and reorganizing hydrogen bonds, the interface integrity is improved, thereby reducing the polarization voltage. In subsequent cycles, due to the stable interface between the self-healing polymer solid electrolyte material based on dodecahydrogen bonds and the electrode, the lithium-lithium battery can show excellent long-cycle characteristics.
[0135] Although the preferred embodiments of the present invention have been described, those skilled in the art will be able to make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0136] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a self-healing polymer solid electrolyte material based on dodecahydrogen bonds, characterized in that: The following steps are involved: Mixing a monomer containing an ether oxygen bond, a diisocyanate, a catalyst and a first solvent, and under the action of the catalyst, polymerizing the monomer containing an ether oxygen bond and the diisocyanate to generate carbamate, thereby obtaining a polymer solution; Adding a pyridine diamine compound and a second solvent to a polymer solution, and reacting an amino group in the pyridine diamine compound with an isocyanate group in a diisocyanate through a chain extension reaction to generate a urea bond. In the process of forming the urea bond, the amino group and nitrogen atom of the pyridine diamine compound act as a proton donor and a proton acceptor to participate in and form a hydrogen bond. Meanwhile, the pyridine diamine compound introduces a plurality of hydrogen bonding points into the polymer chain, thereby forming a twelve-fold hydrogen bond to obtain a polymer solution; The mass ratio of the monomer containing ether oxygen bond, diisocyanate and pyridine diamine compound is 80-100:8-10:1; Adding lithium salt to the high molecular polymer solution to obtain an electrolyte solution; wherein the mass ratio of the high molecular polymer solution to the lithium salt is 25 to 30:1; The electrolyte solution is coated and then dried to obtain a self-repairing polymer solid electrolyte material based on dodecahydrogen bonds.
2. The method for preparing a self-healing polymer solid electrolyte material based on dodecahydrogen bonds according to claim 1, characterized in that: The pyridine diamine compound is at least one selected from 4-methoxypyridine-2,6-diamine, 2,6-diaminopyridine, 5,5'-diamino-2,2'-bipyridine, 4,4'-diamino-2,2'-bipyridine, and 1,1'(4-methoxypyridine-2,6-diyl)diurea.
3. The method for preparing the self-healing polymer solid electrolyte material based on dodecahydrogen bonds according to claim 1, characterized in that: The polymerization reaction conditions are: stirring at 40°C to 60°C for 6h to 10h under the protection of inert gas.
4. The method for preparing a self-healing polymer solid electrolyte material based on dodecahydrogen bonds according to claim 1, characterized in that: The diisocyanate is selected from at least one of hexamethylene diisocyanate and toluene diisocyanate.
5. The method for preparing the self-healing polymer solid electrolyte material based on dodecahydrogen bonds according to claim 1, characterized in that: The monomer containing ether oxygen bond is selected from at least one of tannic acid, polyethylene glycol, polytetrahydrofuran, polyester polyol, polycaprolactone, polyvinyl alcohol and terminal hydroxyl polybutadiene.
6. The method for preparing the self-healing polymer solid electrolyte material based on dodecahydrogen bonds according to claim 1, characterized in that: The lithium salt consists of an organic lithium salt and lithium nitrate, and the organic lithium salt is selected from lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bis(trifluoromethylsulfonyl imide) or lithium bis(fluorosulfonyl imide).
7. The method for preparing the self-repairing polymer solid electrolyte material based on dodecahydrogen bonds according to claim 6, characterized in that: The mass ratio of the organic lithium salt to lithium nitrate is 10-12:
1.
8. A self-repairing polymer solid electrolyte material based on dodecahydrogen bonds prepared by the preparation method according to any one of claims 1 to 7.
9. The self-healing polymer solid electrolyte material based on dodecaple hydrogen bonds according to claim 8, characterized in that: The thickness of the self-repairing polymer solid electrolyte material based on dodecahydrogen bonds is 50 μm to 200 μm.
10. A solid-state lithium metal battery, characterized in that: It is made of a positive electrode material, a negative electrode material and the self-repairing polymer solid electrolyte material based on dodecaple hydrogen bonds as described in claim 8.
Citation Information
Patent Citations
Solid-state battery self-repairing functional interface layer and construction method
CN112687971A
Method for preparing polyurethane-based composite electrolyte membrane and polyurethane-based composite electrolyte membrane
CN113394446A
Polyurethane elastomer containing metal coordination and disulfide bonds as well as preparation method and self-repairing method thereof
CN114773570A
Preparation method of double-dynamic crosslinking self-repairing polyurea
CN116023624A
Preparation method of solid-state metal battery based on dynamic supramolecular ion conductive elastomer
CN116053595A
Cited By
Boron ester bond / hydrogen bond synergistic self-repairing polymer electrolyte as well as preparation method and application thereof
CN120784473A
Composite solid electrolyte and solid lithium battery
CN121688078A